Methods for coastal monitoring and erosion risk assessment: two Portuguese case studies - Bio, A. (2015)
Coastal zones are naturally dynamic and mobile systems exposed to natural (river flows, waves and storms) as well as human interventions that continuously reshape their morphology. Erosion phenomena related to extreme weather events and sediment scarcity are common, threatening buildings and infrastructures, as well as beaches, ecosystems and valuable wetland; conditions that pose challenges to coastal security and defence. Regular monitoring of coastal areas, assessment of their morphodynamics and identification of the processes influencing sediment transport are thus increasingly important for a better understanding of changes and evolutionary trends in coastal systems. This demands a multi-disciplinary approach involving researchers with expertise in coastal processes and state-of-the-art observation technologies. In this paper state-of-the-art surveying methods for an efficient quantification of changes in coastal environments are described and evaluated, and two NW-Portuguese case studies are presented. Survey methods included: topographic surveys based on terrestrial videogrammetric mobile mapping and aerial photogrammetry; sub-tidal bathymetry with sonar imagery using an Autonomous Surface Vehicle (ASV); as well as field observations, with sediment sampling and beach characterisation. In the first case study erosion/accretion patterns in the Douro estuary sand spit are analysed, considering its breakwater, river flow, wave and wind effects. Prior to the construction of a detached breakwater, the spitâ s morphodynamics was related to extreme river flow events, wave and wind conditions; afterwards the spit stabilized its shape and increased its area and volume. In the second case study the coast of Vila Nova de Gaia was broadly analysed, including the shoreface, foreshore and dunes, the characterization of major features and a short-period analysis of installed dynamics. Results obtained from field data, topographical surveys and numerical wave models were combined for the erosion risk assessment, using a methodology specifically developed for the study area. Both monitoring programs achieved their proposed objectives and provided valuable information to the local authorities, as gathered and processed information constitutes a valuable database for coastal planning and for ICZM purposes. They demonstrate the potential of several approaches, supported by advanced technologies, for the study of complex coastal morphodynamic processes.